Shaykh Mutawalli al-Sha'rawi's Views About Tafsir and I'jaz al-Qur'an: (Descriptive-Analysis Study) - Kusroni Kusroni (UIN Sunan Kalijaga Yogyakarta, 2020)
This paper discusses the views of Shaikh Mutawalli al-Sha'rawi about the interpretation and i'jaz al-Qur'an contained in his book titled al-Tafsir al-Sha'rawi or Khawa> tir al-Sha'rawi. al-Sha'rawi is known as one of the leading modern scholars giving great attention and defense of the Qur'an. His attention to the Qur'an evidently appears in his commentary, a collection of lectures, sermons and studies in various pulpits and scientific forums. The method of delivering ideas taken by al-Sha'rawi in this work is by asking a number of questions about the existence of the i'jaz al-Qur'an, then he gives simple but argumentative answers, both aqliyah and naqliyah. Therefore, from here we know how his views related to interpretation and i'jaz al-Qur'an. Al-Sha'rawi argues that, the prophet of Muhammad is the person who is most worthy of interpreting the Qur'an, because to him al-Qur'an was revealed. So he knows and practices it, and from it the mu‘jizat of the Qur'an was manifested. According to him, the mu‘jizat of the Qur'an is evolutionary and evolves with the times and with the progress of modern science and civilization.[يتكلم هذا الموضوع عن موقف الشيخ متولي الشعراوي حول القرآن وما يتعلق به من تفسير وإعجاز وغيره المكتوب فى كتابه المسمى بـ